Analisis Isi Pesan Pro-Kontra Pengguna Instagram terhadap Berita Hak Merek Citayam Fashion Week - Niluh Wiwik Eka Putri; I Gede Titah Pratyaksa (Calathu: Jurnal Ilmu Komunikasi, 2022)
One of the social media that is widely used by the public is Instagram. Recently, the Citayam Fashion Week phenomenon has become a public conversation so that it becomes a trend. Starting from viral videos circulating on social media such as Instagram. But behind the emergence of this phenomenon caused a polemic for one artist named Baim Wong where Citayam Fashion Week is registered to the Ministry of Law and Human Rights by Baim Wong to be patented. The pros and cons of this incident were not only carried out by some community leaders. Social media facilitates the audience to express satisfaction or dissatisfaction through the comment’s column. The method used is a qualitative method that produces descriptive data in the form of written or spoken words from people and observable behavior. The results obtained in this analysis include (1) pro Instagram user comments on Citayam Fashion Week brand rights news. Several accounts are pro or do agree with Baim Wong's actions such as the @tianaazza41 and @annymarissa6669 accounts with educative message content analysis, then @randika_prawira and @sofaiz1010 with the results of the analysis of the message content being persuasive. Meanwhile, (2) contra Instagram user comments on Citayam Fashion Week brand rights news on the @rekomsahamritel and @bukenglim accounts, it was found that the results of the analysis of the message content were persuasive with the technique of compiling messages filled with emotion appeal. Then on the accounts @alyoudee and @beta_9186 found the results of the analysis of the content of messages that are persuasive. Keywords: message content analysis, pro and con, Instagram, Citayam Fashion Week, brand right